Responses of exogenous bacteria to soluble extracellular polymeric substances in wastewater : a mechanistic study and implications on bioaugmentation - Wu, Yichao (2021)
Compared with the chemically defined synthetic wastewater (SynWW), real wastewater has been reported to exhibit distinct effects on microbial community development. Whether and how soluble microbial products in real wastewater contribute to different effects of synthetic and real wastewater on the fate of exogenous bacteria remains elusive. In this study, using a model wastewater bacterium Comamonas testosteroni, we first examined the influences of microfiltration filter-sterilized real wastewater (MF-WW) and SynWW on the retention of C. testosteroni in established wastewater flocs during bioaugmentation. In bioreactors fed with MF-WW, augmentation of C. testosteroni to wastewater flocs resulted in a substantially higher abundance of the augmented bacterial cells than those fed with SynWW. To identify the soluble microbial products in MF-WW contributing to the observed differences between bioaugmentation reactors fed with MF-WW and SynWW, we examined the effect of MF-WW and SynWW on the growth, floc formation, and biofilm development of C. testosteroni. When C. testosteroni grew in MF-WW, visible flocs formed within 2 h, which is in contrast to cell growth in SynWW where floc formation was not observed. We further demonstrated that the observed differences were mainly attributed to the high molecular weight fraction of the soluble extracellular polymeric substances (EPS) in MF-WW, in particular, proteins and extracellular DNA. The DLVO analysis suggested that, in the presence of soluble EPS, the bacterial cell surface exhibits an increased hydrophobicity and a diminished energy barrier, leading to irreversible attachment of planktonic cells and floc formation. The RNA-seq based transcriptional analysis revealed that, in the presence of soluble EPS, genes involved in nonessential metabolisms were downregulated while genes coding for Cco (cbb3-type) and Cox (aa3-type) oxidases with different oxygen affinities were upregulated, facilitating bacterial survival in flocs. Taken together, this study reveals the mechanisms underlying the contribution of soluble EPS in real wastewater to the recruitment of exogenous bacteria by microbial aggregates and provides implications to bioaugmentation.